Analisis Budaya Organisasi dalam Menumbuhkan Motivasi Kerja Karyawan dalam Konteks Perusahaan Modern: Studi Kasus Usaha Sapiring Sale Pisang Kering - Marshanda Arifka Rahmadani; Nilawati Fiernaningsih (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
In this dynamic and competitive modern business era, employee work motivation is an important element in maintaining and improving company performance. Modern companies are full of global competition and complex dynamics, it is very important to understand how a strong organizational culture can be the basis for retaining and motivating employees. This research aims to analyze organizational culture in fostering employee work motivation in the context of a modern company with a case study conducted in the marketing and sales section of the Dried Banana Sapiring Sale Business. The data collection techniques used were observation and interviews. The data obtained was analyzed using qualitative analysis techniques. The research results show that a strong organizational culture can increase employee work motivation. A strong organizational culture is characterized by values ​​shared by all employees, such as integrity, cooperation and innovation. Apart from that, a strong organizational culture is also characterized by the existence of clear policies and procedures, as well as rewards and recognition for good employee performance. In this research, it was found that the era of globalization had a significant impact on employee work motivation. Therefore, companies need to develop a strong organizational culture to increase employee work motivation in the era of globalization.